The Role of Chemistry in Fracture Pattern Development and Opportunities to Advance Interpretations of Geological Materials. (13th September 2019) - Laubach, S. E.; Lander, R. H.; Criscenti, L. J.; Anovitz, L. M.; Urai, J. L.; Pollyea, R. M.; Hooker, J. N.; Narr, W.; Evans, M. A.; Kerisit, S. N.; Olson, J. E.; Dewers, T.; et al.
Abstract: Fracture pattern development has been a challenging area of research in the Earth sciences for more than 100 years. Much has been learned about the spatial and temporal complexity inherent to these systems, but severe challenges remain. Future advances will require new approaches. Chemical processes play a larger role in opening‐mode fracture pattern development than has hitherto been appreciated. This review examines relationships between mechanical and geochemical processes that influence the fracture patterns recorded in natural settings. For fractures formed in diagenetic settings (~50 to 200 °C), we review evidence of chemical reactions in fractures and show how a chemical perspective helps solve problems in fracture analysis. We also outline impediments to subsurface pattern measurement and interpretation, assess implications of discoveries in fracture history reconstruction for process‐based models, review models of fracture cementation and chemically assisted fracture growth, and discuss promising paths for future work. To accurately predict the mechanical and fluid flow properties of fracture systems, a processes‐based approach is needed. Progress is possible using observational, experimental, and modeling approaches that view fracture patterns and properties as the result of coupled mechanical and chemical processes. A critical area is reconstructing patterns through time. Such data sets are essential for developing and testing predictive models. Other topics that need work include models of crystal growth and dissolution rates under geological conditions, cement mechanical effects, and subcritical crack propagation. Advances in machine learning and 3‐D imaging present opportunities for a mechanistic understanding of fracture formation and development, enabling prediction of spatial and temporal complexity over geologic timescales. Geophysical research with a chemical perspective is needed to correctly identify and interpret fractures from geophysical measurements during site characterization and monitoring of subsurface engineering activities. Plain Language Summary: Fracture patterns in rock strongly affect directions, magnitudes, and heterogeneities of both fluid flow and rock strength. Accurate and testable predictions of patterns are essential for understanding many societally important processes in the Earth and for effectively managing subsurface engineering operations. Chemical processes play a larger role in opening‐mode fracture pattern development than has hitherto been appreciated. For fractures formed at depths of ~1–10 km and temperatures of 50–200 °C, new evidence shows chemical reactions are common and more diverse than previously recognized. We describe how viewing fracture formation and evolution from a chemical perspective helps to solve problems in fracture pattern analysis. We outline the main impediments to subsurface fracture pattern measurement and interpretation, assess implications of recent discoveries in fracture history reconstruction for process‐based models of fracture and cement accumulation, review models of fracture cementation and chemically assisted fracture growth, and discuss promising paths for future work. Potential exists for basic scientific investigations to lead to progress on what has been one of the most refractory practical problems in subsurface science. Results suggest that progress in fracture interpretation and prediction can be made using observational, experimental, modeling, and theoretical approaches that view fracture patterns as the result of coupled mechanical and chemical processes. Key Points: A chemical perspective helps solve challenges to understanding subsurface fractures: inadequate samples, ambiguous analogs, and difficulties determining which models are correct from observations Many tools of chemical analysis, experiment, modeling, and theory have yet to be brought to bear on understanding how fracture patterns develop at geological timescales Chemical and mechanical investigations together have great potential to solve challenging practical problems in subsurface science